" State of Knowledge of CSR Practice in Mining Companies in Africa " - Karambiri, Ganabo Lacina (Archives of Business Research, 2021)
This work is inspired by a number of observations or knowledge. Africa is rich in natural resources exploited by mining companies whose impact is damaging. The question of Corporate Social Responsibility (CSR) in the region therefore arises acutely. The reflection on CSR practice in mining companies in Africa allows to have a better visibility of the activity and the state of the existing texts, laws, standards, directives and principles which frame it. African countries implementing the EITI principles must publish annual reports on the status of revenue and payments of taxes, licenses and fees to local governments and the State. The application of international, regional and national instruments makes it possible to better organize the activity, and to formalize the responsibility of the miners in order to instill the development desired by the populations. Of the many possible determinants of responsible action, the authors describe the role that the network can play in managerial learning.